2020
DOI: 10.21203/rs.3.rs-15993/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous Integrated Boost of intensity modulated radiation therapy to Stage II-III Non-Small Cell Lung Cancer with metastatic lymph nodes

Abstract: Background: Local tumor failure remains a major problem after radiation-based nonsurgical treatment for unresectable locally advanced Non-Small Cell Lung Cancer (NSCLC)and inoperable stage II NSCLC .The aim of this study was to evaluate the feasibility of Simultaneous Integrated Boos of intensity modulated radiation therapy (SIB-IMRT) to Stage II-III NSCLC with metastatic lymph nodes. Methods: Patients were diagnosed by pathology or PET-CT. PTV was divide into two parts as follow, the PTV of primary tumor (PTV… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…However, their reported case numbers are very low and FU time rather short, so one should await the results of their ongoing phase II trial. Li et al reported on 20 patients treated with IMRT for inoperable stage II-III NSCLC with metastatic lymph nodes [21]. They treated their patients with a total dose of 78 Gy and 60-65 Gy for the primary and the metastatic lymph nodes, respectively, prescribed simulta- By contrast, fiercely escalated hypofractionation to the primary tumor or subregions of high FDG-uptake in concurrent or sequential CRT has been shown to be feasible, but associated with higher acute and late toxicities compared to conventional CRT [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, their reported case numbers are very low and FU time rather short, so one should await the results of their ongoing phase II trial. Li et al reported on 20 patients treated with IMRT for inoperable stage II-III NSCLC with metastatic lymph nodes [21]. They treated their patients with a total dose of 78 Gy and 60-65 Gy for the primary and the metastatic lymph nodes, respectively, prescribed simulta- By contrast, fiercely escalated hypofractionation to the primary tumor or subregions of high FDG-uptake in concurrent or sequential CRT has been shown to be feasible, but associated with higher acute and late toxicities compared to conventional CRT [22].…”
Section: Discussionmentioning
confidence: 99%